FABRICATION AND CHARACTERIZATION OF TITANIUM DIOXIDE BASED DYE SENSITIZED SOLAR CELL - ANDRE ANDING, TEDONG (Universiti Malaysia Sarawak (UNIMAS), 2019)
In this study, Dye-Sensitized Solar Cells (DSSC) were fabricated using Titanium Dioxide (TiO2) as a metal oxide semiconducting layers dyed with anthocyanin dyed with one type of natural plant extracts. TiO2 solutions with different synthesizing temperatures that are 50 °C, 60 °C, and 70 °C were synthesized using Sol-gel method. The TiO2 solution is deposited on glass substrates using spin coating method. The structural, optical and electrical properties of TiO2 thin film were characterized using scanning electron microscopy (SEM), Ultraviolet -Visible (UV-Vis) spectroscopy, and Current-Voltage (IV) characteristics test. The effects of different synthesizing temperature of TiO2 solution is studied. The structural analysis shows that TiO2 thin film with 60°C of synthesis temperature exhibits the most porous structure and its particle size is smaller if compared to others with synthesis temperature of 50°C and 70°C. Besides that, the optical properties show that TiO2 thin film with 60 °C of synthesis temperature also provide the sharpest peak absorption of 0.40 at the wavelength of 575.50 nm and lower band gap energy of 3.10 eV compared to TiO2 solution synthesized with temperature of 50 °C and 70 °C. The performance of DSSC based on TiO2 synthesized with different temperatures were tested for the electrical properties at two different condition which are light and dark condition. The organic dye used in fabrication of TiO2 based DSSC is beetroot plant that contains anthocyanin extracts. Based on I-V curve results, DSSC sample fabricated with 60 °C of TiO2 solution shows the highest reading of short-circuit current at 0.80 mA and opencircuit voltage at 0.94 V, compared to the DSSC sample with 50 °C and 70 °C synthesizing temperature. The energy conversion efficiency, ɳ for DSSC sample fabricated with 60 °C of TiO2 solution is the highest, that is at 0.316 %, compared to other DSSC sample with 50 °C and 70 °C TiO2 solution that is at 0.158 % and 0.230 %, respectively. Hence, at temperature of 60 °C is the most optimum temperature for synthesizing of TiO2 solution by sol-gel method for DSSC application.